Microplastic Filtration by a Coastal Mangrove Wetland as a Novel Ecosystem Service - Melinda Paduani; Michael Ross; Piero Gardinali (Microplastics)
Biscayne Bay in southeastern Florida, USA, has experienced dramatic ecological declines due to pollution. The Biscayne Bay and Southeastern Everglades Ecosystem Restoration will deliver water from a canal adjacent to coastal mangroves, intercepting pollutants before they are deposited into the estuary. Given their demonstrated capacity to filter nutrients and other contaminants from the water column, we hypothesized that mangrove wetlands also filter microplastics (“MPs”). Water and sediment samples were taken from 3 “zones”: the L-31E canal, a potential MP source; interior, dwarf mangroves; and coastal, tidal fringe mangroves. These three environments were replicated in coastal basins with and without canal culverts. MPs were expected to vary seasonally and be more abundant and larger in the dwarf zone and in low-bulk density sediments as particles settled into peat soils. In sediment, MPs were more abundant in the dry season (average 0.073 ± 0.102 (SD) MPs/g dw) before getting flushed by overland runoff resulting in greater concentrations in water during the wet season (average 0.179 ± 0.358 (SD) MPs/L). MPs were most abundant and larger in the low bulk density sediments of the dwarf zone, likely due to sheltering from fragmentation. Culvert presence had no effect, but MPs may increase as waterflows increase to planned volumes. Understanding MP dynamics enables managers to predict water quality impacts and leverage the potential ecosystem service of MP filtration by mangrove wetlands.